Sanctions Against Perpetrators of Defamation In Law Number 1 of 2023 Concerning Criminal Law Regulations - Rahmides Utami; Irsyad Shabri; Harniwati Harniwati; Gustavianof Gustavianof (Dinasti Research, 2026)
This study aims to determine the sanctions for perpetrators of criminal defamation in Law Number 1 of 2023 concerning Criminal Law Regulations. The Criminal Code (KUHP) regulates the protection of a person's honor and good name through provisions regarding the crime of defamation. These provisions aim to prevent and prosecute acts that attack an individual's reputation or dignity in society. Through existing criminal provisions, the KUHP provides legal guarantees for everyone to ensure that their honor and good name are protected. The research specification is descriptive analytical, with a normative juridical approach method, namely a legal research method that analyzes the principles, rules, and norms of laws and regulations, agreements, and legal doctrine. The type of data used is secondary data. The results of the study indicate that the crime of defamation is an act that attacks a person's honor or reputation by accusing something that can be known to the wider community, thus causing moral and social harm to the victim. In the Indonesian criminal law system, defamation was previously regulated in Articles 310-321 of the old Criminal Code and was later updated in the new Criminal Code through Law Number 1 of 2023. In the new Criminal Code, these provisions are regulated, among others, in Article 433 and other related articles, covering various forms of insult, slander, false accusations, and false accusations, which carry the threat of criminal sanctions in the form of imprisonment or fines. This regulation demonstrates that Indonesian criminal law continues to protect the honor and good name of individuals as part of personal rights that must be upheld in social life.